The politics of the climate change-health nexus - Jungmann, Maximilian (Routledge, Taylor & Francis Group, 2021)
Cover -- Endorsements -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- List of tables -- List of abbreviations -- Acknowledgements -- Preface -- PART I: Introduction -- 1. Between crisis and long-term challenge -- 2. Politics and the nexus between climate change and health -- 3. The explanatory model -- PART II: The global perspective -- 4. Research design -- 5. The CHAIn index -- 6. Regression results -- PART III: The national perspective -- 7. Qualitative research design and case selection -- 8. The United Kingdom of Great Britain and Northern Ireland -- 9. The Republic of Ireland -- 10. The Republic of Korea -- 11. Japan -- 12. Sri Lanka -- 13. General findings -- PART IV: Conclusion -- 14. Main findings -- 15. From the climate crisis to the health crisis and vice versa - a COVID-19 update -- 16. Insights for policymakers -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift